(untitled) (Research, Society and Development, 2023)
Introduction: Paracoccidioidomycosis is a systemic fungal infection caused by the fungi Paracoccidioides brasiliensis (P. brasiliensis) and Paracoccidioides lutzii (P. lutzii), which live as definitive hosts in armadillos, dogs and humans. It is acquired through the handling of contaminated soil or debris, entering via inhalation and systemically affecting multiple organs – and is a rare pediatric condition. Objective: To report a pediatric clinical case of paracoccidioidomycosis in the pediatric intensive care department of the Hospital Universitário Maria Aparecida Pedrossian (HUMAP). Methodology: Observational, descriptive, narrative and reflective study, clinical case report type. General data were obtained through the electronic medical record, after approval by the Research Ethics Committee. Results: Patient, male, 6 years old, with chronic daily fever associated with postprandial vomiting, diarrhea, hyporexia, weakness, weight loss, increased abdominal volume and lung involvement. He was referred to the pediatric infectious diseases service at HUMAP, where he was diagnosed with paracoccidioidomycosis. The patient was treated with liposomal amphotericin B, progressing with clinical improvement and allowing medical discharge with outpatient return. Although the patient was not in the commonly affected age group, he presented a positive history of rural exposure and highly suggestive clinical symptoms. The case had multiple correlations with the literature review carried out, proving that the service carried out correct conduct. Conclusion: It is concluded that it is necessary to know the disease to investigate it within infectious diseases, as well as the importance of recording cases for organizing appropriate public policies.